2019
DOI: 10.1101/730549
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying genetic effects on disease mediated by assayed gene expression levels

Abstract: Disease variants identified by genome-wide association studies (GWAS) tend to overlap with expression quantitative trait loci (eQTLs). However, it remains unclear whether this overlap is driven by mediation of genetic effects on disease by expression levels, or whether it primarily reflects pleiotropic relationships instead. Here we introduce a new method, mediated expression score regression (MESC), to estimate disease heritability mediated by the cis-genetic component of assayed steady-state gene expression … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
52
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 105 publications
5
52
1
Order By: Relevance
“…Our results suggest that sex-specific eQTLs in whole blood do not translate to detectable sex-specific trait associations, and vice versa that the observed sex-specific trait associations cannot be explained by sex-specific eQTLs. While a recent work revealed that ~11% of trait heritability could be explained by cis-eQTL regulation [26], our findings show that the sex-specific heritability is not detectably mediated by sex-specific gene expression regulation. Our extensive power analyses, performed using a range of realistic effect sizes, confirmed these observations.…”
Section: Discussioncontrasting
confidence: 84%
“…Our results suggest that sex-specific eQTLs in whole blood do not translate to detectable sex-specific trait associations, and vice versa that the observed sex-specific trait associations cannot be explained by sex-specific eQTLs. While a recent work revealed that ~11% of trait heritability could be explained by cis-eQTL regulation [26], our findings show that the sex-specific heritability is not detectably mediated by sex-specific gene expression regulation. Our extensive power analyses, performed using a range of realistic effect sizes, confirmed these observations.…”
Section: Discussioncontrasting
confidence: 84%
“…Finally, these methods assume that genetic risk for disease is mediated through regulation of gene expression. Yet, recent evidence suggests that the overall proportion of disease heritability mediated by cis-eQTLs is much lower than previously thought, around w10% in SCZ at least with current bulk tissue reference panels (66). The missing signal may be explained by distal QTLs, by missing cis-eQTLs for lowly expressed genes (e.g., ncRNAs), by those not captured in bulk tissue (cell typespecific QTLs) (23,67), or in distinct biological contexts, such as the fetal brain (37).…”
Section: Prioritization Of Target Genes and Proximal Mechanisms Undermentioning
confidence: 70%
“…Systematic colocalisation efforts based on GTEx data have identified putative target genes for 47% of the GWAS loci (3). Still, these genetic effects mediate only 11% of disease heritability (4), suggesting that many regulatory effects cannot be detected in bulk tissues at a steady-state (5). In contrast, profiling specialised disease-relevant cell types such as induced pluripotent stem cells (6), peripheral immune cells (7), microglia (8,9) or dopaminergic neurons (10) often identifies additional colocalisations that are missing in GTEx.…”
Section: Introductionmentioning
confidence: 99%